2002
DOI: 10.2307/3072042
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Asymmetric Competition: A Case Study with Two Larval Anuran Species

Abstract: Abstract. The outcome of interspecific competition may be modulated by a large number of factors, both biotic and abiotic. In this paper, we examined experimentally the effects of geographic variation, population density, and abiotic stress on the outcome of interspecific competition between two species of larval anurans. Three different populations of natterjack toad (Bufo calamita) were set to compete with common toad (Bufo bufo) in replicated artificial ponds under different combinations of osmotic stress (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
(65 reference statements)
1
9
0
Order By: Relevance
“…Our findings on competition are consistent with previous studies that have demonstrated strong asymmetric interspecific effects on the fitness-related parameters of tadpoles (e.g., Heusser, 1972aHeusser, , 1972bSmith-Gill and Gill, 1978;Wilbur, 1982Wilbur, , 1987Morin and Johnson, 1988;Griffiths, 1991;Griffiths et al, 1991;Werner, 1992;Semlitsch, 1993;Kupferberg, 1997;Parris and Semlitsch, 1998;Bardsley and Beebee, 2000;Gurevich et al, 2000;Relyea, 2000;Dayton and Fitzgerald, 2001;Gómez-Mestre and Tejedo, 2002;Smith et al, 2004;Smith, 2005). Our results, however, showed a pattern different from that detected in previous studies of desert anuran communities, in which active ephemeral pool species have a competitive advantage over less active species from temporary or permanent ponds (Woodward, 1982;Dayton and Fitzgerald, 2001).…”
Section: Discussionsupporting
confidence: 54%
“…Our findings on competition are consistent with previous studies that have demonstrated strong asymmetric interspecific effects on the fitness-related parameters of tadpoles (e.g., Heusser, 1972aHeusser, , 1972bSmith-Gill and Gill, 1978;Wilbur, 1982Wilbur, , 1987Morin and Johnson, 1988;Griffiths, 1991;Griffiths et al, 1991;Werner, 1992;Semlitsch, 1993;Kupferberg, 1997;Parris and Semlitsch, 1998;Bardsley and Beebee, 2000;Gurevich et al, 2000;Relyea, 2000;Dayton and Fitzgerald, 2001;Gómez-Mestre and Tejedo, 2002;Smith et al, 2004;Smith, 2005). Our results, however, showed a pattern different from that detected in previous studies of desert anuran communities, in which active ephemeral pool species have a competitive advantage over less active species from temporary or permanent ponds (Woodward, 1982;Dayton and Fitzgerald, 2001).…”
Section: Discussionsupporting
confidence: 54%
“…These results were independent of the use of any sibship size prior, thus supporting the reliability of mating system inferences. Epidalea calamita lays clutches in ephemeral puddles (therefore reducing interspecific but increasing intraspecific competition), taking advantage of their fast larval development (Gómez-Mestre & Tejedo, 2002). Immediate occupancy of these ephemeral sites after heavy rainfalls is therefore critical for maximizing the opportunities for larvae to survive until metamorphosis.…”
Section: Mating System Inferencesmentioning
confidence: 99%
“…Euryhaline tadpoles of Fejervarya cancrivora (formerly known as Rana cancrivora), which live in mangrove swamps experiencing wide salinity fluctuations (Alcala, 1962;Gordon and Tucker, 1965;Dunson, 1977;Uchiyama et al, 1990), can tolerate extremely high salinity (≥35 ppt) but suffer developmental retardation to the point of preventing metamorphosis (Gordon, 1961;Gordon and Tucker, 1965;Dunson, 1977;Uchiyama et al, 1990). Delayed time to metamorphosis incurs an increased risk of desiccation (Newman, 1992;Gomez-Mestre and Tejedo, 2002) and predation (Alford, 1999).…”
Section: Introductionmentioning
confidence: 96%